Water conservation measures in buildings: a comparative study between rainwater harvesting and greywater use - Pimentel-Rodrigues, Carla; Silva-Afonso, Armando (Frontiers in Environmental Science, 2025)
Portugal, a Mediterranean country in southwestern Europe, presents a worrying future concerning the availability of fresh water, essentially due to climate change. According to data from the Portuguese Institute of Meteorology (IPMA), the average annual temperature could rise by three degrees within two or three decades, and annual precipitation will reduce by between 20% and 25% in the territory. For the rational management of drinking water in urban areas, Portugal should adopt a fundamental principle called the “5R principle”: Reduce consumption, reduce losses and inefficiencies, reuse water, recycle water, and resort to alternative sources. In order to achieve efficient use of drinking water in buildings and reduce consumption, installing efficient devices must always be the priority technical measure. Rainwater harvesting or using regenerated greywater is generally considered a complementary drinking water conservation measure. Typically, these non-potable waters have a potential for competitive uses (flush toilets, washing, etc.), so the simultaneous adoption of these two measures is generally not considered, although this is feasible. In this article, a comparative analysis is made between these two measures for a single-family house in the Central Region of Portugal, weighing technical, economic and sanitary aspects and considering the construction rules adopted in Portugal. For rainwater harvesting, a conventional system is considered, and for the use of treated (or regenerated) greywater, a building system for the use of treated greywater (or greywater recovery system) is considered. In either case, the uses considered for non-potable water will be the same: flush toilets, watering a small garden and washing clothes. The results show that the choice between these two drinking water conservation measures must be assessed in each specific situation, weighing the technical, sanitary and economic constraints.